PELAKSANAAN PROGRAM PARENTING DI TAMAN KANAK-KANAK DI KOTA PONTIANAK - Khairiyah, Rahayu; Fadillah, Fadillah; R, Marmawi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe aim of this research was to describe the implementation of the parenting program in Pontianak City Kindergarten. The method use isn this research is descriptive method with a quantitative research approach. Population in this research are all kindergarten in Pontianak City that have used the parenting program, totalin 80kidergarten. The sample in the implementation of parenting program in kindergartens in Pontianak City amounted to 62 kindergartens. The techniques used in this research were used of questionnaires and documentation using data collection tools like is a questinneaire, and documentation picture. The results of data analysis show describe the implementation of the parenting program in Pontianak City Kindergarten, the most widely used parenting program model was the parent group meeting model, the parenting material used is about improving nutrition, health care, education, ad protection, the inhibiting factor in the implementation of parenting program is the limitied time parents have.Keyword          : Parenting Material, Parenting Program, The Implementation